2016
DOI: 10.3389/fphar.2015.00326
|View full text |Cite
|
Sign up to set email alerts
|

The Extract of Roots of Sophora flavescens Enhances the Recovery of Motor Function by Axonal Growth in Mice with a Spinal Cord Injury

Abstract: Although axonal extension to reconstruct spinal tracts should be effective for restoring function after spinal cord injury (SCI), chondroitin sulfate proteoglycan (CSPG) levels increase at spinal cord lesion sites, and inhibit axonal regrowth. In this study, we found that the water extract of roots of Sophora flavescens extended the axons of mouse cortical neurons, even on a CSPG-coated surface. Consecutive oral administrations of S. flavescens extract to SCI mice for 31 days increased the density of 5-HT-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Moreover, SF or its compounds have been shown to have anti-oxidative (Piao et al, 2006 ), anti-cancer (Sun et al, 2007 ; Liu et al, 2010 ), anti-arthritic (Jin et al, 2010 ), anti-ulcerative (Yamahara et al, 1990 ) and anti-dermatitis (Kim et al, 2012 ) effects, and recent studies have shown that it has neuroprotective effects. Extract of SF suppressed sodium nitroprusside-induced apoptosis in SH-SY5Y cells, while focal cerebral ischemia induced neuronal death in rats (Park et al, 2009 ) and enhanced axonal growth in mice (Tanabe et al, 2015 ), and oxymatrine extracted from SF prevented neuronal cell death in rat brains subjected to cerebral ischemia-reperfusion damage (Li et al, 2011 ). However, it is still not known if SF can also protect DA.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, SF or its compounds have been shown to have anti-oxidative (Piao et al, 2006 ), anti-cancer (Sun et al, 2007 ; Liu et al, 2010 ), anti-arthritic (Jin et al, 2010 ), anti-ulcerative (Yamahara et al, 1990 ) and anti-dermatitis (Kim et al, 2012 ) effects, and recent studies have shown that it has neuroprotective effects. Extract of SF suppressed sodium nitroprusside-induced apoptosis in SH-SY5Y cells, while focal cerebral ischemia induced neuronal death in rats (Park et al, 2009 ) and enhanced axonal growth in mice (Tanabe et al, 2015 ), and oxymatrine extracted from SF prevented neuronal cell death in rat brains subjected to cerebral ischemia-reperfusion damage (Li et al, 2011 ). However, it is still not known if SF can also protect DA.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we found that the water extract of dried roots of Sophora flavescens , a traditional medicine used in China, Korea, and Japan, enhanced axonal growth of cultured cortical neurons on a CSPG coating (Tanabe et al, 2016 ). Administration of S. flavescens extract to SCI mice increased axonal density [5-hydroxytryptamine (5-HT)-positive tracts] at the lesion site and improved the motor dysfunction.…”
Section: Introductionmentioning
confidence: 98%
“…Sophora flavescens Aiton, the shrubby sophora, belongs to the family Fabaceae (Leguminosae) and is an important legume in Asia [3]. The root of S. flavescens, also known as Kosam in Korean (Kushen in Chinese), is commonly used as a traditional herbal medicine because of its various biological activities, including anti-cancer, anti-arrhythmic, anti-allergic, anti-inflammatory, and anti-asthmatic effects [3][4][5][6]. It has been officially listed in the Korean Pharmacopoeia and Chinese Pharmacopoeia.…”
Section: Introductionmentioning
confidence: 99%